PENGARUH ATRIBUT PRODUK DAN KETIDAKPUASAN KONSUMEN TERHADAP KEPUTUSAN PERPINDAHAN MEREK MELALUI BRAND IMAGE SEBAGAI VARIABEL INTERVENIG PADA SEPEDA MOTOR MERK A KE SEPEDA MOTOR MERK B DI YOGYAKARTA - Handalu, Prayoga Rinno (Politeknik Negeri Jakarta, 2021)
To purpose is : (1) To determine the effect of product attributes on brand image, (2) To determine the effect of dissatisfaction on brand image, (3) To determine the effect of product attributes on brand shift, (4) To determine the effect of dissatisfaction on brand shift, ( 5) To determine the effect of brand image on brand movement This type of research is quantitative research, the population in this study is 100 motorbike users A who switch to motorbikes B. The sample used is 100 motorbike users A who use motorbikes B. The sampling method used was accidental sampling with the Arikunto formula. Data collection using a questionnaire. The analysis method used is multiple regression supported by the t-test. The results of the analysis show that product attributes have a significant positive effect on brand image, consumer dissatisfaction has a significant positive effect on brand image, product attributes have a significant positive effect on brand transfer, consumer dissatisfaction has a significant positive effect on brand transfer, brand image has a significant positive effect on brand transfer, attributes The product has a significant positive effect on brand movement through brand image as an intervening variable, consumer dissatisfaction has a significant positive effect on brand movement through brand image as an intervening variable. Keywords : Product attributes, dissatisfaction, Brand shift, and brand image.